Welfare beyond the state: ‘ihsani’ societal-based welfare - Malik, Maszlee (The Institute of Economic Affairs, 2016)
This does not lead to the creation of an imaginary, utopian society based purely on theory without consideration for reality. To achieve their goals, individuals will actively be working to promote society’s ‘well-being’ and the creation of ‘social capital’, or ihsani capital. Indeed, these things are currently accepted by many people who are not Muslim as an effective aspect of the promotion of economic development, equality, participation and democracy. Increasing evidence shows that social cohesion is critical for societies to prosper economically and for development to be sustainable.